Pelaksanaan Fungsi Dinas Kependudukan dan Pencatatan Sipil Kota Jambi Dalam Penerbitan Akta Kematian di Wilayah Kota Jambi - Nuraini Nuraini; Mhd Ansori; Andini Nur Pratiwi (Universitas Batanghari Jambi, 2020)
A death certificate is one of the civil registration deeds that lack public awareness in reporting the processing of a death certificate due to the lack of public understanding of the function of a death certificate. Jambi City is one of the areas where the people are not very enthusiastic about registering a Death Certificate with the Population and Civil Registration Office of Jambi City. Until now, there are still many people who ignore or do not understand the importance of death certificates because they think that processing a death certificate is difficult and requires money. This paper aims to identify and analyze the implementation of the function of the Jambi City Population and Civil Registration Service in issuing death certificates in the city of Jambi. The type of research used is empirical juridical research, or with a research approach, data sources, techniques. data collection, and techniques for sampling and data analysis. Based on the results of the research, it is known that the implementation of the function of the Jambi City Population and Civil Registration Service in issuing death certificates in the city of Jambi has been running according to the prevailing laws and regulations and according to the circular received from the Central Government and Regional Government.